ATRA upregulates OTUD6B to recruit CD8+ T cells to suppress colorectal liver metastasis by stabilizing DDX5/STAT3/CXCL11 axis - Jinglei Li; Kunpeng Huang; Bing Yang; Xia Hu; Bosheng Mei; Xiang Cheng; Xin Zhong; Chuyi Cao; Zihan Chen; Hui Wang; Jinxiang Zhang (Cell Death and Disease)
Abstract OTU deubiquitinase 6B (OTUD6B) study in tumors is gradually increasing; however, studies on the role of OTUD6B in colorectal cancer (CRC) are rare. OTUD6B was overexpressed in some human CRC and liver metastasis samples. Although OTUD6B facilitated migration and invasion in CRC cells, it exhibited opposite effects on liver metastasis in immunodeficient and immunocompetent mice. We demonstrated that Otud6b enhanced metastasis in nude mice, but it recruited more CD8+ T cell infiltration in colorectal liver metastasis (CRLM) mouse model of C57BL/6J to inhibit CRLM through upregulating Cxcl11. Furthermore, we demonstrated that OTUD6B deubiquitinated and stabilized DDX5. Ectopically expressed DDX5 facilitated transcription factor STAT3 activation by resolving the RNA G-quadruplex structure of STAT3, resulting in a higher level of CXCL11 transcription and an increase in tumor-infiltrating CD8+ T cells. All-trans retinoic acid inhibited CRLM by upregulating OTUD6B.